Analisis Psikometris The Moral Injury Scale - Aulia, Yasmin Siti; Jayadinata, Aditya; Greene, Ally Allena; Wyandini, Diah Zaleha; Hidayat, Ghinaya Ummum Mukminin (Journal of Research and Measurement in Psychology: JPPP, 2025)
This study aims to develop a valid and reliable measurement tool for assessing moral injury among university students in higher education settings. Moral injury is defined as the psychological impact resulting from violations of deeply held moral values, potentially leading to guilt, shame, and existential crises. The developed instrument was tested through item analysis, validity, and reliability assessments. Results indicated that all items had item-total correlations above 0.30 and factor loadings ≥ 0.40, demonstrating psychometric validity. Reliability, measured using Cronbach’s α, achieved a score of 0.963, indicating a very high level of consistency. However, model fit analysis revealed that the instrument did not fully meet the model fit criteria (GFI = 0.811; RMSEA = 0.089). Despite this, the instrument successfully categorized respondents into five levels of moral injury, with the majority classified as moderate (40.1%). These findings highlight the need for further model refinement and the development of psychological interventions to support student well-being. This study makes a significant contribution to educational psychology literature and provides a foundation for improving measurement tools to assess moral injury more effectively. Keywords: Moral Injury, Validity, Reliability, Model Fit, University Students, Psychological Measurement Tools.